Mobile health technology combats COVID-19 in China - Wu, Jieyu (J Infect, 2021)
China empowers mobile health technologies to fight against COVID-19 pandemic. The success of mobile health here may be a useful reference for other parts of the world. We explore China's application of mobile health technologies to replenishing traditional public-health and social approaches for mitigating and suppressing COVID-19, and found that Internet hospitals alleviate the unavailability, inaccessibility, and inequity of health services during the outbreak; the fact-check and information-release platforms reduce the spread of misinformation; and the infection risk scoring systems facilitate restoring the order of production and life.